Pengaruh Promosi Kesehatan Terhadap Perubahan Perilaku Hidup Bersih dan Sehat Tatanan Rumah Tangga Di Dusun IV Desa Lawolatu Kecamatan Ngapa Kabupaten Kolaka Utara - Irna; Andi Yusuf; Muhammad Rifai (NERSMID : Jurnal Keperawatan dan Kebidanan, 2022)
Clean and healthy living behavior (PHBS) is a collection of behaviors that are carried out on the basis ofawareness as a result of learning that makes someone who makes a person able to help himself in the healthsector and plays an active role in realizing the health of his community. The purpose of the study was todetermine the effect of health promotion on changes in clean and healthy lifestyles in householdarrangements in Hamlet IV, Lawolatu Village, Ngapa District, North Kolaka Regency. The type of researchused is Quasy-Experiment with non-equivalent control group design, the sample in this study is divided into2, namely 20 people as the experimental group and 20 people as the control group using spiral samplingtechnique and questionnaires as research instruments. The results showed that changes in PHBS in terms ofwashing hands with clean water and soap with p value = 0.000, using clean water with p value = 0.007, usinglatrines with p value = 0.001, eradicating larvae with p value = 0.004, physical activity with p value = 0.001,not smoking in the house with p value = 0.004 Conclusion obtained There is an effect of changing PHBSwashing hands with clean water and soap using clean water, using healthy latrines to eradicate larvae athome, doing physical activity, not smoking inside house before and after receiving intervention, researchsuggestions are expected to raise public awareness, especially in the household environment in PHBS as aneffort to prevent disease